Dynamics of changes in the structural components of the mucosa and cartilage of the larynx of rats at the end of 42 days of experimental opioid exposure and after 56 days with opioid withdrawal - Ivasivka, Khrystyna (Journal of Education, Health and Sport, 2021)
In our work we aimed to study the pathomorphological manifestations among the structural components of the laryngeal mucosa and cartilage in the later stages of the experimental opioid effect. This goal was achieved through the use of histological techniques to visualize the structural components of the laryngeal mucosa and cartilage. Histological sections with a thickness of 5 -7 mm were made. Histological specimens were prepared according to conventional methods using the dye hematoxylin, eosin, azan according to the method of Heidenhain, PAS-reaction according to Mc-Manus and Alcian blue according to Steedman. Microscopic examinations and photographing of the preparations were performed using an MBI-1 microscope and a Nicon D 3100 digital camera. At the end of 42 days of experimental exposure, the epithelial layer of the epiglottis was inhomogeneously thickened, with excessive accumulation on its pharyngeal and apical part of the stratum corneum. Individual epitheliocytes of the pharyngeal part of the epiglottis underwent necrotic changes, the horny substance loosened in places. On the pharyngeal surface of the mucous membrane found a small amount of mucus with impurities of erythrocytes. Dyscirculatory processes were also registered in the animals of the experimental group. In particular, dilatation and overflow of erythrocytes of vessels of own plate of a mucous membrane of an epiglottis, and also polymorphonuclear infiltration of own plate of a mucous membrane were observed.